NABI IDRIS DALAM PERSPEKTIF KITAB-KITAB SUCI AGAMA DAN KETOKOHANNYA DALAM KAJIAN ILMU FALAK - Novi Arizatul Mufidoh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2020)
The term prophet comes from Arabic, with the origin of the word naba’, which is usually interpreted as news, and stories. In the history of the world, the prophet has always been synonymous with the discussion of a special person by the God who delivered the message to guide his people, as well as smart people who teach humans about various disciplines to worship and understand their God. There are many prophets who have been sent to the world with different disciplines. Among astronomers, one of the prophets who were featured was Idris as. Because, as part of the name of the prophet who must be believed in Muslims, Idris as was one of the most important people in the study of Falak science (science of astronomy), because a lot of literature explains that he was the first human who discovered astronomy. This article is the result of the analysis literature study provides an explanation regarding the biography of the prophet Idris and his genealogy contained in several holy books, namely the Torah, the Bible, and the Qur'an. Besides that, some astronomers in his book stated that the prophet Idris as was the inventor of astronomy. Keyword: Idris as, Falak Science, Holy Books